A theology of gratitude for rising generations - Townes, Stephanie (Anglican theological review, 2021)
Rising generations (Millennials and Gen Z) already have a solid understanding of gratitude from gratitude’s pervasiveness in popular culture, and because of this, gratitude is an opportunity for the Church to reach rising generations where they already are. To do this, the Church should underscore a theological why of gratitude and a practical theological how of gratitude. The theological why of gratitude is based on Kathryn Tanner’s gift-giving nature of God, from her book Jesus, Humanity, and the Trinity. The practical theological how of gratitude will rise up from our holy habits of gratitude, both personal and collective, reinforced by the Eucharist, and taught through discipleship and practices of stewardship.